Systematic review with meta‐analysis: efficacy and safety of oral Janus kinase inhibitors for inflammatory bowel disease. Issue 1 (23rd May 2019) - Ma, Christopher; Lee, Jeffrey K.; Mitra, Anish R.; Teriaky, Anouar; Choudhary, Daksh; Nguyen, Tran M.; Vande Casteele, Niels; Khanna, Reena; Panaccione, Remo; Feagan, Brian G.; Jairath, Vipul
Summary: Background: Janus kinase (JAK) inhibitors represent a novel therapeutic class for treatment of inflammatory bowel disease. Aims: To determine the efficacy and safety of JAK inhibitors compared to placebo for the treatment of Crohn's disease (CD) and ulcerative colitis (UC). Methods: PubMed, Embase and CENTRAL were systematically searched to November 1, 2018. Randomised placebo‐controlled trials (RCTs) of JAK inhibitors in adult patients with CD or UC were eligible. Open‐label extension studies without a placebo comparator arm were excluded. Clinical, endoscopic, and safety outcomes were extracted and rates relative to placebo were pooled using a random‐effects model. Results: A total of 12 RCTs (5 CD, 7 UC) were included. Patients were randomised to placebo (n = 844), tofacitinib (n = 1882), filgotinib (n = 130), peficitinib (n = 176), upadacitinib (n = 387) or TD‐1473 (n = 31). JAK inhibitor treatment was associated with induction of clinical remission in CD (RR, relative risk 1.38 [95% confidence interval CI 1.04‐1.83], P  = 0.025, I 2  = 14%) and UC (RR 3.07 [95% CI 2.03‐4.63], P  < 0.001, I 2  = 0%). In UC, JAK inhibitor treatment was associated with induction of endoscopic remission (endoscopic Mayo subscore MCSe = 0/1) (RR 2.43 [95% CI 1.64‐3.59], P  < 0.001, I 2  = 27%) and mucosal healing (MCSe = 0) (RR 5.50 [95% CI 2.46‐12.32], P  < 0.001, I 2  = 0%). JAK inhibitor treatment increased the risk of infection compared to placebo (RR 1.40 [95% CI 1.18‐1.67], P  < 0.001, I 2  = 0%), particularly for herpes zoster. Conclusions: JAK inhibitors are effective for inducing clinical remission in CD and induction of clinical and endoscopic remission in UC, although are associated with an increased risk of infectious complications.